2006
DOI: 10.1158/1078-0432.ccr-06-0386
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization by Dietary Docosahexaenoic Acid of Rat Mammary Carcinoma to Anthracycline: A Role for Tumor Vascularization

Abstract: Purpose: To investigate whether dietary docosahexaenoic acid (DHA), a peroxidizable polyunsaturated N-3 fatty acids, sensitizes rat mammary tumors to anthracyclines and whether its action interferes with tumor vascularization, a critical determinant of tumor growth. Experimental Design: Female Sprague-Dawley rats were initiated by N-methylnitrosourea to develop mammary tumors and then assigned to a control group (n = 18), receiving a supplementation of palm oil, or to a DHA group (n = 54), supplemented with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 34 publications
7
58
0
2
Order By: Relevance
“…This trial is a logical extension of earlier studies carried out in rodents and shows that a defined food component, namely DHA, can turn malignant mammary tumours from resistant to sensitive to chemo- (Colas et al, 2006) or radiation therapy (Colas et al, 2004). Our data show for the first time that a dietary intervention targeted on DHA is a feasible approach that has potential to substantially increase survival in metastatic breast cancer patients treated with chemotherapy.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This trial is a logical extension of earlier studies carried out in rodents and shows that a defined food component, namely DHA, can turn malignant mammary tumours from resistant to sensitive to chemo- (Colas et al, 2006) or radiation therapy (Colas et al, 2004). Our data show for the first time that a dietary intervention targeted on DHA is a feasible approach that has potential to substantially increase survival in metastatic breast cancer patients treated with chemotherapy.…”
Section: Discussionsupporting
confidence: 65%
“…Using cultured breast cancer cell lines, it was reported that pre-enrichment of these cells with DHA enhanced their sensitivity to a variety of anti-cancer classes of drugs (Begin et al, 1986;Menendez et al, 2005;Wang et al, 2007) and more specifically to anthracyclines, an oxidative stressinducing anti-cancer drug with a quinone structure (Germain et al, 1998;Mahéo et al, 2005). Furthermore, a prolonged (several weeks) supplementation with DHA (fish oil or algae-derived DHA), initiated before and continued during chemotherapy, consistently increased the sensitivity of autochthonous mammary tumours to anti-cancer drugs (Shao et al, 1997;Hardman et al, 2001;Colas et al, 2005Colas et al, , 2006. Similar results have been observed with radiation therapy (Colas et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both have been described to increase the therapeutic efficacy of RT in breast cancer cell lines, 8 rodent model 9 and also in patients. 10 In CRC, EPA or DHA, on its own, inhibits HT-29 cell growth, but DHA is more efficient than EPA due to its rapid cellular absorption and integration into cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…These microdomains cluster together proteins involved in the regulation of crucial cellular processes; many of which are altered in cancer cells (Pike, 2003;de Laurentiis et al, 2007). Furthermore, lipid rafts are readily modified by diet and nutrition (Schley et al, 2007;Yaqoob, 2009), and studies have shown that fatty acid supplementation sensitises human mammary tumour cells to the cytotoxic effects of anti-cancer agents in vitro and in vivo (Germain et al, 1998;Menendez et al, 2005;Colas et al, 2006). This chapter will focus on the potential regulatory functions of lipid rafts as a novel approach towards understanding mechanisms of cancer initiation, progression and cell migration, a key event preceding metastatic progression.…”
Section: Introductionmentioning
confidence: 99%